Forest land prone to more soil erosion than cultivated land in the Chure hill of eastern Chitwan, Nepal - Oli, B.; Khanal, B. R.; Lamichhane, S.; Ojha, R. B. (Journal of Agriculture and Forestry University, 2020)
This study was done at Lothar-Pampha Watershed, located in the Chure hill of eastern Chitwan, inside the boundary of Rapti Municipality covering 121.83 km2 (12183.12 ha). The main objective of the study was to estimate the spatial distribution and the extent of soil erosion in the watershed using Geographic Information System (GIS) and Remote Sensing (RS) tool. Annual average soil loss was estimated by using the Revised Universal Loss Equation (RUSLE), RSdata using GIS platform, taking spatial variation of each factors. Data on Rainfall erosivity (R), Soil erodibility (K), slope length and steepness (LS), cover crops (C) and soil conservation practices (P) were calculated from laboratory analysis and also retrieved from Landsat image. Soil sample were taken to determine the K factor from the 71 different areas inside the research boundary of Rapti Municipality. Rainfall data of 21 years from 21 different nearby stations were taken from the Department of Hydrology and Meteorology, Nepal (DHM). The soil erosion was categorized into seven classes as, extremely severe (>190 t ha-1 year-1), very severe (100-190 t ha-1 year-1), severe (50-100 t ha-1 year-1), high (10-50 t ha-1 year-1), moderate (5-10 t ha-1 year-1), slightly (2-5 t ha-1 year-1), and very slightly (0-2 t ha-1 year-1) that occurred in 0.0043 %, 0.0862 %, 0.98 %, 29.71 %,18.34 %, 13.54 %, and 37.31 % of total area of Lothar-Pampha watershed, respectively. The total soil erosion estimated from the forest area (70.11 %) was 89537.29 t year-1 whereas from grasslands area (0.25 %) it was estimated as 81.03 t year-1, and from the agricultural land (18.10 %) it was 1529.52 t year-1. The maximum erosion rate (275.36 t ha-1 year-1) was estimated in the forest area followed by grasslands (22.19 t ha-1 year-1). Average soil erosion rate in settlement area was estimated as 0.27 t ha-1 year. Likewise, 8.87 % of total erosion was estimated from the agricultural land. Forested land is seemingly contributing to more soil erosion than agricultural land due to steep land topography, poor conservation program, deforestation, and unscientific forest management practices which seek for scientific forest management plan including soil conservation measures such as grass waterways, terracing, contouring, strip-cropping in Lothar-Pampha watershed of the Chure range.